KUALITAS BATUGAMPING BERDASARKAN ANALISIS KLASIFIKASI GEOMEKANIK DI GOA SEROPAN, GUNUNG KIDUL, YOGYAKARTA - Nugroho, Bani; Pranantya, Pulung Arya; Utomo, Edi Prasetyo (Bulletin of Scientific Contribution, 2016)
Seropan cave is one of the caves in Semanu sub District, located in the karst region, Gunung Kidul, Yogyakarta. Based on reserach of Karlsruhe Institut of Teknology (KIT) German, is known underground river in the cave is very potential to be developed. Underground dams and micro hydro installations built to pump water upwards the river. These are used as raw water for daily needs and irrigation in the surface.  For this purpose it is necessary to study the stability of the rock mass in the cave Seropan. The stability of a tunnel or cave is heavily influenced by geological and non-geological factors. The most dominant geological factors in general are geological structures, can be muscular or fault, the type of rock and rock mass quality.The rocks at the cave Seropan in general are limestones. Based on rock mass classification of Rock Mass Rating (Bieniawski, 1989) otherwise known as the geomechanics classification, these rocks are included in class III and class IV. These rocks include moderate to bad quality. Until now the cave conditions remained relatively stable and secure. This is due to the naturally formed cave. The process of distribution of stresses around the cave coincided with the formation of caves and takes place in a relatively long time. However, in some parts of the cave should be because the effect of fractures can lead to collapse of the roof of the cave.